2015
DOI: 10.1186/s40064-015-1001-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of anemia in a multi-ethnic chronic kidney disease population: a case–control study

Abstract: Anemia is a common complication of chronic kidney disease (CKD). However, risk factors of anemia in CKD patients in Singapore are not well established. Hence, a retrospective, case–control study involving non-dialysis CKD patients was conducted to determine possible predictors of anemia in the local CKD population.Non-dialysis adult CKD patients, not receiving renal replacement therapy or erythropoiesis-stimulating-agents were included. Parameters collected included demographics e.g. age, sex and race; clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 45 publications
5
20
3
Order By: Relevance
“…Similar findings have been reported from other studies conducted in low-and middle-income countries, whereby hypertension has been reported to be the leading cause of CKD. 2,9,10,13,14 However, these findings are contrary to a community-based study conducted in Northern Tanzania that showed that nearly half (49.2%) of the cases of CKD were not associated with any of the measured risk factors of hypertension, diabetes, or HIV. 16 This discrepancy calls for more research into other causes of CKD, including the use of local herbs and medicines, which is very rampant in this area where this study was conducted.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Similar findings have been reported from other studies conducted in low-and middle-income countries, whereby hypertension has been reported to be the leading cause of CKD. 2,9,10,13,14 However, these findings are contrary to a community-based study conducted in Northern Tanzania that showed that nearly half (49.2%) of the cases of CKD were not associated with any of the measured risk factors of hypertension, diabetes, or HIV. 16 This discrepancy calls for more research into other causes of CKD, including the use of local herbs and medicines, which is very rampant in this area where this study was conducted.…”
Section: Discussioncontrasting
confidence: 77%
“…In a hospital study conducted in Singapore, researchers found that 87.7% of patients had moderate to severe CKD 13 ; while in another hospital study conducted in Nigeria, found the overall prevalence to be 18.8%. 14 CKD was at least 3 to 4 times more frequent in Africa than in developed countries.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to other medical complications, anemia dominates for the accumulation damage course of cerebral autoregulation. With the progress of the disease, patients with anemia will suffer from many complications, such as heart failure 31 , chronic kidney disease 32 and vascular endothelial cells 33 34 , which play a more important role than anemia in the development of stroke. This effect may partly explain why Sico and colleagues found a positive relationship in patients with less severe stroke but not in severe stroke 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients in Stage 5 compared to Stage 4 DKD had significant low level of Hb along with significant low level of Vitamin D and high level of iPTH which is consistent with other studies. [ 9 10 ] However, with significantly high TSAT (Stage 5 vs. Stage 4), Hb was low which may be due to impaired iron release from body stores that is unable to meet the demand for erythropoiesis (also called reticuloendothelial cell iron blockade).…”
Section: Discussionmentioning
confidence: 99%